THE ROLE OF LEADERSHIP, COMPENSATION, AND TRAINING IN ORDER TO ENHANCE THE EMPLOYEE PERFORMANCE AT PT. ADHIMIX RMC INDONESIA - Budi Jatmiko; Charles Bohlen Purba (Dinasti International Journal of Education Management And Social Science, 2021)
This research aims to revealed and look over the impact which caused by the training, compensation and leadership style towards the employee performance at PT. Adhimix RMC Indonesia. This research were in type of causality research with a quantitative research methods. The data collection technique in this research was an explanatory survey method with the population was 1328 people with filtered sample to 100 respondents (Slovin, 10% error tolerance). The data analysis method used was multiple linear regression analysis in way to examine the research hypothesis. The results showed that training, compensation, and leadership style had an influence both partially and simultaneously towards the employees performance at PT. Adhimix RMC Indonesia.